Strings of Connectedness. Essays in honour of Ian Keen - Toner, P.G (ANU Press, 2015)
For nearly four decades, Ian Keen has been an important, challenging, and engaging presence in Australian anthropology. Beginning with his PhD research in the mid-1970s and through to the present, he has been a leading scholar of Yolngu society and culture, and has made lasting contributions to a range of debates. His scholarly productivity, however, has never been limited to the Yolngu, and he has conducted research and published widely on many other facets of Australian Aboriginal society: on Aboriginal culture in 'settled' Australia; comparative historical work on Aboriginal societies at the threshold of colonisation; a continuing interest in kinship; ongoing writing on language and society; and a set of significant land claims across the continent. In this volume of essays in his honour, a group of Keen's former students and current colleagues celebrate the diversity of his scholarly interests and his inspiring influence as a mentor and a friend, with contributions ranging across language structure, meaning, and use; the post-colonial engagement of Aboriginal Australians with the ideas and structures of 'mainstream' society; ambiguity and indeterminacy in Aboriginal symbolic systems and ritual practices; and many other interconnected themes, each of which represents a string that he has woven into the rich tapestry of his scholarly work.